STRATEGI KEPEMIMPINAN OTENTIK UNTUK MENINGKATKAN KREATIVITAS POOKDARWIS DESA WISATA SUKAJADI, KABUPATEN BOGOR, JAWA BARAT - Yuviani Kusumawardhani; Aggy Lestari (Bogor Hospitality Journal, 2023)
The trend of rural tourism after the Covid-19 pandemic in Indonesia has increased along with the emergence of new economic tourism. However, the development of rural tourism tourism is still slow with a large number of pilot rural tourism, especially in Bogor Regency, West Java Province, compared to other provinces in Java Island. The crucial problems that occur in the development of rural tourism in Bogor Regency are human resources and institutions, so the urgency of this research is that the rural tourism of Bogor Regency require strengthening tourism through empowering the human resources of creative tourism awareness groups (Pokdarwis) through authentic leadership roles. The purpose of this research is to strengthen tourism human resources that are globally competitive based on Pokdarwis empowerment through authentic leadership strategies to increase creativity. The research method used is qualitative with SWOT analysis. The sampling technique used was purposive sampling with six (6) expertise. This research resulted in eight authentic leadership strategies to increase the creativity of Sukajadi tourism village Pokdarwis so that Sukajadi tourism village Pokdarwis can be globally competitive and able to have innovation and avoid duplication of tourist attractions.